Pengaruh Konsumsi Minuman Khusus Ibu Pengaruh Konsumsi Minuman Khusus Ibu Hamil terhadap Kecukupan Zat Gizi Makro Ibu HamilHamil terhadap Kecukupan Zat Gizi Makro Ibu Hamil - Irgananda, Anisa Ilhami; Sartika, Ratu Ayu Dewi; Nuryandari, Primasti (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Background: Macronutrients are needed in greater amounts by pregnant women to meet their own nutritional needs as well as for fetal growth and development. Commercial milk formula formulated with special nutritional content for pregnant women are widely circulated in the community, so it is necessary to study the adequacy of macronutrients from the consumption of these products and their compliance with the requirements and information on the product label. Objective: To determine the relationship between consumption of commercial milk formula-pregnant and nutritional status, to compare macronutrient intakes between pregnant women who consume commercial milk formulapregnant and those who do not, and to provide an overview of the contribution of macronutrient intakes derived from that product to the values set as product standards. Methods: Cross-sectional study in Sawangan Subdistrict, Depok City on 225 pregnant women selected by total sampling. Data were analyzed univariately and bivariately using chi-squared to assess the influence between the independent variable and the dependent variable, and independent t-test to compare the nutritional intake of the group who consumed commercial milk formula-pregnant with those who did not. Results: The habit of consuming commercial milk formula-pregnant was significantly associated with energy, fat and protein deficiencies (p≤0.05). Macronutrient intakes were higher among mothers consuming commercial milk formula-pregnant than among nonconsumers, with average macronutrient intakes from prenatal beverages being in accordance with the nutrient requirements and RDAs listed in nutrition facts on the product label. Conclusion: The study results can be used as a reference for evaluating standard regulations and product monitoring as well as public health recommendations, especially for pregnant women's nutrition.